2015
DOI: 10.3109/03639045.2015.1115868
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction study between flavanones (hesperetin, naringenin) and rasagiline mesylate in wistar rats

Abstract: Cytochrome P-450 (CYP) enzymes and P-glycoprotein (P-gp) play an important role in the oral bioavailability and first-pass-metabolism (FPM) of many drugs. Rasagiline is a selective, monoamine oxidase-B inhibitor and it undergoes significant FPM in the liver prior to excretion by CYP1A2. Hesperetin and naringenin are naturally occurring flavanones and are reported as modulators of CYP enzymes and P-gp. The objective of the present investigation was to evaluate the effect of hesperetin and naringenin on the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…At the same time, herbs may also affect CYP450 enzymes, and the flavonoids are among the most important. Hesperetin can affect CYP1A2, and quercetin can affect CYP3A4, CYP2C9, CYP1B1 and CYP1A1 (Chen et al 2009;Pingili et al 2016;Jana and Rastogi 2017;Palle and Neerati 2018). Naringenin is an aglycone of naringin; it has previously been reported that naringenin can inhibit CYP3A4 (Liu J et al 2019).…”
Section: Analytementioning
confidence: 99%
“…At the same time, herbs may also affect CYP450 enzymes, and the flavonoids are among the most important. Hesperetin can affect CYP1A2, and quercetin can affect CYP3A4, CYP2C9, CYP1B1 and CYP1A1 (Chen et al 2009;Pingili et al 2016;Jana and Rastogi 2017;Palle and Neerati 2018). Naringenin is an aglycone of naringin; it has previously been reported that naringenin can inhibit CYP3A4 (Liu J et al 2019).…”
Section: Analytementioning
confidence: 99%
“…Se lavó con solución salina fisiológica fría. Para la eversión del intestino, se siguió la técnica descrita por Wilson y Wiseman (17) y reproducida por otros investigadores (18)(19)(20) , que fue modificada para este estudio, reemplazando el material de la varilla, que era de acero inoxidable, por polietileno, con aumento ligero de la longitud (Figura 2). Inmediatamente después de extraer la pieza de intestino y everterla con una varilla de polietileno (1,5 mm, 350 mm), se colocó en una placa petri con solución salina, adecuada oxigenación y temperatura a 37 °C.…”
Section: Eversión De Los Sacos Intestinalesunclassified
“…In this regard, it is noteworthy, that the ABCB1 function weakening verapamil is well known as onset of idiopathic PD onset facilitating or PD syndrome inducing compound [7]. There is no interaction between ABCB1 function and the MAO-B inhibiting compounds selegiline, rasagiline, and safinamide [9,10]. All of them reduce oxidative stress.…”
Section: May Chronic Application Of Pd Drugs Influence Abcb1 Transpormentioning
confidence: 99%